Productive characteristics of forage crops for supplementation in milk production systems, Nariño, Colombia: Evaluacion forrrajes - Nieto-Sierra, David Felipe (2020)
Introduction. Grass is the main source of feed for ruminants, however, it is not able to provide the nutrients required for its maintenance and productivity, added to this, in the high tropics is very noticeable the seasonality of fodder production, so it is very important to know other feeding alternatives. Objective. Characterize and evaluate ten forage crops as alternative sources of supplementation in milk production systems in the high tropic of Nariño. Materials and methods. The study was carried out in three localities (L1, L2 and L3) representative of the milk basin of the department of Nariño between november 2016 and september 2017. A Random Complete Blocks (BCA) design was used with ten treatments Vicia faba (espadrille), Vicia faba (red), Vicia faba (common), Zea mayz var. ICA V-305, Raphanus sativus L., Beta vulgaris, Avena sativa var. Cayuse, Phalaris sp., Medicago sativa L. var. moapa, Medicago sativa L. var. 10 10, three repetitions and comparison of averages to 0.05. A the time of harvest it was estimated: green forage yield and dry matter, crude protein (PC), neutral detergent fibre (FDN)), acid detergent fibre (FDA), lignin, hemicellulose, dry matter digestibility, and net lactation energy (ENL). Results. The outstanding species were the bean (the three varieties) and fodder beet for its yield and nutritional quality, which presented values between 7.48 and 20.24 % for PC and 1.14 and 1.49 Mcal kg-1 for ENL. Differences between treatments were presented for each locality, both in productive and nutritional variables. Conclusion. The forage species with the highest productive yield and nutritional quality were the three bean varieties (red, common, and espadrille) and beet.